Interventional Pain Management in Degenerative Spine Disorders: A Case Report - Hutagalung, Muhammad Bayu Zohari (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Low back pain (LBP) is a common health issue affecting a significant portion of the population, particularly adults aged 35-55 years. Nearly 70-80% of individuals in developed countries experience LBP at some point in their lives. We reported a 54-year-old female presenting with LBP persisting for one year. Her pain predominantly occurs during walking, is limited to 100 meters, and is characterized by gripping sensations in the thigh and calf, exacerbated by positional changes but relieved with rest. Imaging revealed anterior listhesis of the L4 vertebral body relative to L5 (<25%) and multiple bulging discs at various lumbar levels, most notably severe at L4-5 with moderate central and severe bilateral neural foraminal stenosis. The patient underwent Selective Nerve Root Block (SNRB) and facet joint blocks with local anesthetic and steroid medication, resulting in a reduction of pain complaints and decreased leg numbness post-intervention. Understanding and addressing specific spinal pathologies in this case was expected to guide effective treatment strategies to alleviate symptoms and improve patient function.